UPAYA PENGURANGAN POLUTAN DARI MESIN S.I. DENGAN MEMANFAATKAN ZEOLIT - Yuniarto Agus Winoko; Bambang Irawan; Bambang Sulistiyono (Universitas Lambung Mangkurat, 2014)
Zeolites including absorbent types that can absorb exhaust emissions of combustion are not stochiometri, through the activation process consists of physical and chemical processes. Zeolite powder which has been active subsequently compacted and placed in the vehicle exhaust. The purpose of the research to determine how much change the optimum emissions, minimum and average of carbon monoxide (CO) and hydrocarbons (HC) are mounted in a standard exhaust from extensive contacts zeolite catalyst 1300, 1760, 2260cm2. In addition, to determine how large the percentage change in the optimum power, minimum and average of 1486cc engine when installed catalyst with extensive contacts with the standards. How large is the current AFR optimum and minimum reduction CO, HC, and the power generated. Test method for the activation of the catalyst using the BET and testing of power, torque, emissions of CO and HC engine valve opening fully to start the engine rev up to 4000rpm stationary. Large volumes of fuel 100ml, with a range of changes in the engine rotation 500rpm for each test.The results showed a large reduction of 45.54 optimum.%, Minimum 44.00.% And the average CO at 44.97.% While the HC reduction of 31.44%, minimum, optimum average of 33.33% and 32.44% to the 3000 standard round for CO and HC 2500 for wide when contact 1760cm2. 9.31% decline optimum power, minimum of 6.83% and an average of 7.86% at 14.78 AFR and 3000rpm.Keywords: carbon monoxide, hydrocarbon, power